Investigation of price formation in different commodities in the seaborne trade : crude oil - Tan, Samuel Wei Khang (2016)
Changes in oil prices often make the headlines, and for good reason. Not only does it reflect the state of the global economy, it is a vital source of the global energy demand. It is one of the most closely monitored commodities simply because it has ramifications for many around the world. This paper aims to study, among other times, the fundamentals that make up the oil economy as well as triggers that cause immense changes in oil price. If there is one word that sums up the oil market in its present context, it would be dynamic. Over the years, prices have taken spikes and tumbles in a cyclical fashion and such changes have a wide span of ramifications to say the least. Following the strong growth between 2003 and 2008 came the biggest oil price shock in recent memory accompanied the 2008 financial crisis that plunged the world into a rapid downward spiral. Speculation has played a major role in intensifying price changes. Since then, oil prices have struggled to even come close to the highs of 2008. Recovery of the oil price has been hampered by the factors such as the shale gas revolution, increased focus on renewable energy, supply gluts and Saudi Arabia’s refusal to alter her production. Along the way, anticipation and speculation of supply shocks pertinent to the Arab Spring and Libyan Civil war have caused spikes in the oil prices. Looking forward, gone are the days where prices were at the mercy of the OPEC the alpha. The U.S. shale gas revolution and Russian crude oil market share tug-of-war have posed worthy competition to the status quo. Further, incongruence exists among the rank of OPEC, with different countries seeking different goals, leading to a less than united voice from the powerhouse. With the global economy headed for continuous growth, it is unlikely oil prices will stay at its current low.